Aplicabilidad de la exoneración por costas notariales y registrales en el Ecuador en el caso de adultos mayores - Brito Borja, David Marcelo (2026)
The present work entitled: “Applicability of the exoneration for notary and registry costs in Ecuador in the case of older adults”; whose line of research includes “Civil Law and its relation with Notary and Registry Law”, has a great relevance to the extent that the number of older adults is increasingly higher in the country, demanding that domestic legislation effectively guarantee their rights and guarantees established in our Constitution. The objective of this work was thus focused on verifying the level of compliance with the exoneration of notary and registry fees for senior citizens as provided in Art. 306 of the Organic Code of the Judicial Function, in relation to the Notarial Law in force, the procedures in which it is applied and the percentage in which it must be done. For this purpose, the analytical-critical method was used, first identifying the problem to be solved, then separating it into sub-problems that do not allow understanding each of its elements, in order to subsequently establish specific criteria, created on the basis of theory, doctrine and established legislation. As a result of the effort of this work, it can be highlighted that there are still procedures whose costs have an impact on the economy of the elderly, preventing them in some cases to access them; this not only shows a lack of updating in terms of the number of procedures that should be considered but also a flagrant violation of their rights established in our Constitution.